The Humbling Effect of Significant Relationships: A Field Experiment Examining the Effect of Significant-Other Activation on Leaders’ Expressed Humility - Wang, Lin; Li, Junchao (Jason); Owens, Bradley P.; Shi, Lihua; Wang, Mo (Organization Science, 2024)
Recent research has consistently highlighted the benefits of leader humility within organizations. However, much less is known about how leader humility can be contextually promoted beyond individual predispositions. This paper draws from the social-cognitive model of transference to illuminate how the contextual activation of significant-other schemas can enhance a leader’s expressed humility in the workplace. Specifically, we propose that the activation of significant-other schemas can lead to increased interpersonal warmth and psychological safety among leaders, which in turn, promote humility in their interactions with followers. Furthermore, we posit that these effects are amplified in leaders who possess a strong relational identity. To test our hypotheses, we conducted a field experiment with 97 leaders and their 194 followers, where we randomly applied daily significant-other activation interventions to the leaders and surveyed the leaders and their corresponding followers across 10 consecutive workdays. Our findings provide support for the positive impact of significant-other schema activation on leader humility and confirm the moderating role of a leader’s relational identity. We discuss the theoretical and practical implications of our findings. Funding: This research was supported by the National Natural Science Foundation of China [Grants 72022022 and 72332009] and the John Templeton Foundation [Grant 62265] entitled “Applied Research on Intellectual Humility.” Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.17377 .